On the power of childhood impressions for skill formation: Initial evidence and unsettled questions - Friedhelm Pfeiffer (Institute for the Study of Labor (IZA), 2013)
Manifold childhood impressions result from the interactions with adult caregivers and the environment. These impressions, be they beneficial or detrimental, shape individual skill formation and achievement over the life cycle. The novelty of the paper is that it bonds two different, hitherto separated, research lines, one from economics, one from psychology, to discuss the relationship between childhood impressions and later achievement. First, selected recent findings on early life adversity and skill formation are presented. Second, a tool for improving self-regulation, called implementations intentions, is introduced, which may have the power to counteract negative childhood impressions later in live. The attempt to integrate the two approaches results in a discussion of unsettled questions and an outlook for future research.
Keywords: D87; I12; I21; J13; 330; early life adversity; implementation intentions; life cycle; skill formation